Marilyn Strathern, Before and after gender: Sexual mythologies of everyday life, Chicago, Chicago University Press, 2016, pp. 280 - Alessandra Gribaldo (Anuac, 2017)
Book review of Marilyn Strathern, Before and after gender: Sexual mythologies of everyday life, Chicago, Chicago University Press, 2016, pp. 280.